Dinosaur Mummies: Beyond Bare-Bone Fossils - Halls, Kelly Milner (Plain City, OH Darby Creek Publishing, 2003)
More than bones and teeth, these recent dino discoveries include fossilized skin, muscles, hearts, stomachs, and more!
6 - 8
Keywords: Dinosaurs; Fossils